2007
DOI: 10.1016/j.ejcts.2007.01.069
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord ischemia after elective endovascular stent-graft repair of the thoracic aorta☆

Abstract: Background: We reviewed our experience to investigate the determinants of paraplegia/paraparesis after endovascular stent-graft repair of the thoracic aorta, to assess the influence of the artery of Adamkiewicz (ARM) detected by preoperative magnetic resonance angiography (MRA) and to identify patients at risk. Methods: Over a 5-year period (March 2001-June 2006, 149 patients underwent elective endovascular stentgraft repair of the descending thoracic aorta. Patient demographics and perioperative factors relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 21 publications
(37 reference statements)
1
33
1
Order By: Relevance
“…Buth J, Harris PL, Hobo R et al [8] made the following statement "independent correlation with SCI was observed for 4 factors [1] left subclavian artery covering without revascularisation (odds ratio [OR], 3.9; p = 0.027), [2] renal failure (OR, 3.6; p = 0.02), [3] concomitant open abdominal aortic surgery (OR, 5.5; p = 0.037) and [4] 3 or more stent grafts used (OR, 3.5; p = 0.043). Some of these findings were confirmed by Kawaharada N, Morishita K, Kurimoto Y et al [9] concluded "Prior thoracic aortic replacement was found to be a significant predictor of spinal cord ischemia". Amabile P, Grisoli D, Giorgi R et al [10] in an experience of 67 patients concluded "Multivariate logistic regression analysis showed that length of aortic coverage was the only independent significant predictor of SCI.…”
Section: What Are the Risk Factors For Spinal Cord Ischaemiasupporting
confidence: 69%
“…Buth J, Harris PL, Hobo R et al [8] made the following statement "independent correlation with SCI was observed for 4 factors [1] left subclavian artery covering without revascularisation (odds ratio [OR], 3.9; p = 0.027), [2] renal failure (OR, 3.6; p = 0.02), [3] concomitant open abdominal aortic surgery (OR, 5.5; p = 0.037) and [4] 3 or more stent grafts used (OR, 3.5; p = 0.043). Some of these findings were confirmed by Kawaharada N, Morishita K, Kurimoto Y et al [9] concluded "Prior thoracic aortic replacement was found to be a significant predictor of spinal cord ischemia". Amabile P, Grisoli D, Giorgi R et al [10] in an experience of 67 patients concluded "Multivariate logistic regression analysis showed that length of aortic coverage was the only independent significant predictor of SCI.…”
Section: What Are the Risk Factors For Spinal Cord Ischaemiasupporting
confidence: 69%
“…We previously reported that prior aortic surgery was identifi ed as a signifi cant risk factor for spinal cord ischemia. 9 Based on our data, patients in this study must be at high risk for spinal cord ischemia because every patient with anastomotic pseudoaneurysm underwent open aortic surgery. In fact, we did not utilize spinal cord protection with spinal drainage or maintain a high systolic blood pressure; and there were no postoperative neurological complications, such as paraplegia or paraparesis in our study.…”
Section: Discussionmentioning
confidence: 97%
“…Basically, the 20 F or 22 F delivery sheath was inserted from the common femoral artery (Table 2). In two patients (cases 7,9), the femoral artery was too small to accommodate the delivery sheath; hence, a retroperitoneal incision was performed to insert the delivery sheath via the iliac artery. In the event that a stent-graft was placed on a proximal portion of the aortic arch, a fenestrated stent-graft was employed to preserve adequate blood fl ow to the brain (cases 2, 6,7,8).…”
Section: Patient Populationmentioning
confidence: 99%
“…It is still controversial that the collateral vessels can feed blood into the spinal cord, 13,15 and occlusion of the artery of Adamkiewicz may not be the only causative factor aŠecting spinal ischemia. 16 However, actual cases of spinal cord ischemia after endovascular repair of the aorta continue to be reported, 17 and increase in biochemical markers of ischemic spinal cord injury was documented in an experimental canine study of stent-graft implantation at a critical aortic segment. 18 Our study demonstrated that the artery of Adamkiewicz can be detected at a high rate preoperatively, allowing evaluation of the risk of occlusion of this artery, which could aŠect the likelihood of spinal complications.…”
Section: Discussionmentioning
confidence: 99%